PENERAPAN KONSELING BEHAVIORISTIK DENGAN TEKNIK SELF MANAGEMENT UNTUK MENGATASI PENYALAHGUNAAN MEDIA SOSIAL OLEH SISWA KELAS VII SMP 2 GEBOG KUDUS - Dyah Ayu Saputri; Masturi Masturi; Indah Lestari (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
This study aims: 1.To describe what factors make seventh grade students of SMP 2 Gebog able to abuse social media. 2. To assist seventh grade students in overcoming social media abuse through behavioristic counseling with self-management techniques at SMP 2 Gebog Kudus. The subjects studied were 2 seventh grade students of SMP 2 Gebog Kudus who abused social media. Methods of data collection using the method of observation, interviews, documentation, and home visits. Based on the results of the study, it can be concluded that there are two factors that cause social media abuse, namely internal and external, there are several factors that cause BM and RDA to abuse social media, including: lack of attention from parents, conflicts with friends, wanting to get attention from the opposite sex. , lack of confidence and fad. This makes BM and RDA behave maladaptively, say rude or swear, post pornographic things that harm others. After counseling with a behavioristic approach and self-management techniques, BM and RDA were able to eliminate their maladaptive behaviors such as being able to manage their thoughts and actions, control their emotions so they don't say rude things on social media and become confident. That means that behavioristic counseling and self-management techniques are very appropriate to overcome the abuse of social media experienced by BM and RDA.